Plurality of Voices in Reflecting Upon the Research Process: Trajectories of Collaboration in an Argentinian Setting - Porto, Melina (2022)
This article describes the trajectories of collaboration experienced by three individuals in three different roles (informant, research assistant, and supervisor) in two research projects about English as a foreign language reading in a higher education context in Argentina. Data come from reflection logs and retrospective narratives written by them from 2009 to 2016 which were analyzed using content analysis, focusing on a continuum of collaboration. The article aligns with the critique of the discourse of “newer researcher” as a linear developmental trajectory as it illustrates the participants’ fluid, critical, complex, and personally relevant pathways. Placed within the debate regarding the affordances, complexities and challenges of the measured university, this research contributes perspectives from a peripheral setting generally underrepresented in the literature.